Ecoregion-based height-diameter models for Crimean pine - Seki, Mehmet; Sakici, Oytun Emre (Informa UK Limited, 2021)
Generalized height (h)–diameter (d) models were developed for Crimean pine stands in the Kastamonu Regional Directorate of Forestry, northwestern Turkey. Nine generalized h-d models were fitted and...
Keywords: 15. Life on land